The Continuance Usage Intention of E-Government Services Based on Technology Continuance Theory - Hunneman, Taufan; Napitupulu, Darmawan (Manunggal Halim Jaya, 2025)
The growing adoption of e-Government services, such as Satu Data Indonesia (SDI), requires a deeper understanding of factors that influence the long-term usage of these services. This study aims to explore the continuance usage intention of e-Government services by applying Technology Continuance Theory (TCT). The research examines the roles of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Satisfaction (SAT), and Attitude (ATT) in driving the sustained use of SDI. Data were collected through an online survey involving 175 respondents who have used the SDI platform. The findings reveal that while PU significantly influences both satisfaction and attitude, PEOU only affects PU and does not directly influence attitude. Furthermore, ATT is the strongest predictor of continuance intention (CI), with SAT indirectly influencing continuance intention through ATT. These results suggest that user retention depends more on developing positive attitudes through satisfying experiences rather than solely focusing on system usability or usefulness. The study provides valuable insights for policymakers and service developers to enhance e-Government services for sustained user engagement.